Students’ Perceptions, Practices, and Challenges of Using Instagram and TikTok for English Language Learning - Rossyita Ayu Anggraini (Universitas Negeri Surabaya, 2026)
This study aims to investigate the perceptions of X grade students at state high school in Gresik regarding the use of social media platforms, specifically Instagram and TikTok, to learn English outside the classroom. This study focuses on students’ practices and challenges of using Instagram and TikTok as a tool for language learning. Employing a qualitative research methodology, data was collected through open-ended questionnaire designed to explore X grade students’ experience related to the use of Instagram and TikTok for educational purposes. The result of this study indicate that students perceive Instagram and TikTok as valuable resources for language learning, offering opportunities for authentic language exposure, creative expression, and active interaction. However, the study also highlights several challenges, including technical issues, distractions, and concerns about the reliability of educational content available on these platforms. Consequently, to maximize its benefits, the use of Instagram and TikTok to support learning must be done carefully, with the support of students’ critical thinking skills. Therefore, balanced learning strategies and good digital literacy are needed so that students can effectively utilize both platforms to support their learning journey.